INNOVATION OF THE STUDY COURSE AND MOODLE - MEIER, Miroslav (Trends in education, 2011)
The paper presents details of the project, which was supported by a grant FRVS 1137/2011 in the thematic area F5. The project is focused on innovation General Pedagogy Course, which will be implemented in software, electronic learning environment Moodle.
Keywords: e-learning; innovation; Internet; Moodle; pedagogy; computer; students; education.